LEXICOGRAPHIC ANALYSIS OF THE CONCEPT OF GUILT - SAVCHUK, S. V. (Ehrlich's Journal, 2023)
The article deals with disclosure of relevant attributes of the concept of guilt in linguistic culture: 1) guilt as an ill act for whom the human being shall take the consequences of; 2) guilt as a human being’s state of responsibility for his/her previous ill act. Indirectly, this word is nominated to an ill act whose wrongfulness is realized by a human being (fault, offense, crime); in other cases, it marks the human being’s state of mind when he/she illy acted; the feelings experienced by the same (responsibility, punishment for the ill act, etc.). The guilt as a state of responsibility origins from a previously performed ill act. With that, there is a restriction: it is not to be supposed that decomposing the word guilt into two or even more lexemes one would have units with identical meanings in all contexts. In particular, lawyers and psychologists put the guilt in the first place in the guilt – responsibility scheme. Unlikely, philosophers emphasize on the category of responsibility. Guiltiness in jurisprudence does not seem possible in isolation from human’s responsibility, and, vice versa, responsibility is always guilty. Guilt is the grounds of juridical responsibility. Certainly, in some cases they admit the incurrence of responsibility with no consideration of guilt. However, such responsibility can hardly be regarded as guiltless in the full sense of this word, since the person held responsible with no consideration of his/her guilt has the right of counter demand (remedy over) towards the other person who was the cause of breach of obligations, or who is guilty if, under law, the limits of responsibility of the latter and the person who is responsible for him/her are equal.